Makassar City Government Communication Strategy through the Makassarkota.Go.Id Website in Public Services - Annisa Nurul Firdausi; Yusmanizar Yusmanizar; Andi Vita Sukmarini (Journal of Public Representative and Society Provision, 2026)
This study aims to analyse the Makassar City Government's communication strategy through the makassarkota.go.id website and the Pakinta' (Pajak Terintegrasi & Terdigitalisasi) service. Makassarkota.go.id serves as the leading portal integrating information, policies, and access to 12 public services (including Pakinta'). Pakinta' facilitates online regional tax payments, increasing efficiency, transparency, and taxpayer compliance. The implementation of the Chris Fill (Put, Push, Pull) communication strategy has successfully captured public attention, strengthened internal coordination, and built long-term relationships between the government and the community. The collaboration between the Communications and Information Technology Office (Diskominfo) and the Regional Revenue Agency (Bapenda) has resulted in consistent information, ease of access, and improved quality of digital public services that are faster, more transparent, and more responsive.